Go-Ride Drivers Work Motivation Analysis in PT. Gojek Indonesia (Research on Driver Go-Ride PT. Gojek Indonesia Malang) - Mima Kurniasih; Umar Nimran; Tri Wulida Afrianty (Sekolah Pascasarjana Universitas Brawijaya, 2021)
A start-up company is a phenomenon of business development, based on information technology through digital marketing by using Internet technology, in the form of an application that integrate the owners and users.Â Human resources who are in charge in organization is not only employees, but also partners for business outside the company. Motivation that comes from partners of business is very important to be managed by company, therefore the goals could be carried out well. This study describes and analyzes the work motivation of drivers who are join in PT. Gojek Indonesia in Malang. This research uses a descriptive qualitative, by collecting several data through a triangulation method.Â The collected data would be analyzed by using Miles, Huberman, and Saldana analysis method models.Â The result presents that work motivation of the drivers influenced by individual character and work environment factor. Hence, an organization support that is provided for the drivers is also increase their work motivation, therefore the drivers would like to stay with PT. Gojek Indonesia Meanwhile, to increase work motivation an adjustment is still needed in rewards system that is provided to the drivers.